2021
DOI: 10.23887/jippg.v4i2.35695
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Model Pembelajaran Problem Based Learning Untuk Meningkatkan Hasil Belajar IPA

Abstract: Rendahnya hasil belajar IPA siswa disebabkan oleh kurangnya kegiatan ilmiah pada pembelajaran yang terkait dengan kehidupan nyata. Maka tujuan dari penelitian ini yakni untuk meningkatkan hasil belajar IPA siswa kelas IV melalui penerapan model pembelajaran Problem Based Learning. Penelitian ini merupakan penelitian tindakan kelas yang dilakukan dalam dua siklus melalui tahapan perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian ini adalah siswa kelas IV yang berjumlah 29 orang, terdiri dari 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
0
0
1
Order By: Relevance
“…In addition to project tasks, the study material also includes KKNI tasks such as critical book review, critical journal review, mini-research, case study, idea engineering, and routine tasks. The development of this teaching material is in accordance with the results of research presented by Widura, et al (2021) which said that the Problem Based Learning and Project Based Learning Learning Models can improve student learning outcomes [16].…”
Section: Resultssupporting
confidence: 75%
“…In addition to project tasks, the study material also includes KKNI tasks such as critical book review, critical journal review, mini-research, case study, idea engineering, and routine tasks. The development of this teaching material is in accordance with the results of research presented by Widura, et al (2021) which said that the Problem Based Learning and Project Based Learning Learning Models can improve student learning outcomes [16].…”
Section: Resultssupporting
confidence: 75%
“…In addition to project assignments, teaching materials also contain KKNI tasks such as Critical Book Review, Critical Journal Review, Mini Research, Casus Studies, Engineering Ideas, and Routine Tasks. The development of this teaching material is in accordance with the results of research presented by Widura, et al (2021) who said that the Problem Based Learning and Project Based Learning Learning Models can improve student learning outcomes.…”
Section: Discussionsupporting
confidence: 79%
“…This value shows the average difference between pree test and post test learning outcomes where the difference is between -4.16 to -3.41. This is like the results of research conducted by Widura (2021) which says that problem-based learning models can improve learning outcomes. The same thing is also the opinion of Faqiroh (2020) who found that the use of project-based learning and problembased learning is highly desired by students in improving their competence, so that educators are expected to be able to provide innovation in their learning.…”
Section: The Impact Of Using Organizational Behavior Teaching Materia...supporting
confidence: 66%
“…dalam mengukur kemampuan berpikir kritis yaitu: model ajar yang berfokus pada masalah sehingga dapat meningkatkan keterampilan problem solving, materi serta penguatan diri Adicondro & Anugraheni, 2022). Proses pembelajaran dikatakan aktif jika dalam proses pembelajaran terjadi proses interaksi atau hubungan timbal balik antara guru dengan siswa, siswa dengan siswa lainnya, dan melibatkan siswa secara aktif dalam proses pembelajaran, proses pembelajaran yang demikian dapat dilaksanakan melalui penerapan model pembelajaran Problem Based Learning(Widura, Bayu & Aspini, 2021). Oleh karena itu, penelitian tentang pengaruh model Problem Based Learning terhadap kemampuan berpikir kritis dan hasil belajar IPA di Sekolah Dasar menjadi sangat penting untuk dilakukan.2.…”
unclassified